Identifying healthcare cost drivers in Palestine. (8th March 2021) - Morrar, Rabeh; Jabr, Samer; Ghandour, Rula; Abu‐Rmeileh, Niveen ME; Forgione, Dana A.; Younis, Mustafa
Abstract: We examine the relationship between national health expenditure and its drivers to help inform resource allocation policy decisions in Palestine. We forecast health expenditures from the financing agency perspective, and examine Granger‐Causality relationships to assess implied causality between health spending and exogenous variables, using estimates of vector autoregressions. We forecast national health expenditure to be US$1.45 billion in 2015 and grow at 7% annually through 2020. This is due to expected increases in government health expenditure, and household spending, at 5% and 7%, respectively, compared to 2014. The proportion of household spending on health services is expected to increase, while the government proportion is expected to decrease over the long run due to budget constraints. Population growth, ageing and changes in chronic disease patterns contribute significantly as drivers of the increase in healthcare costs. Our results suggest a need to review and modify the current health insurance scheme.